TaqMan-quantitative PCR assays applied in Neospora caninum knock-outs generated through CRISPR-Cas9 allow to determine the copy numbers of integrated dihydrofolate reductase-thymidylate synthase drug selectable markers - Rico-San Román, Laura; Hänggeli, Kai Pascal Alexander; Hemphill, Andrew; Horcajo, Pilar; Collantes-Fernández, Esther; Ortega-Mora, Luis Miguel; Boubaker, Ghalia (Frontiers in Cellular and Infection Microbiology, 2024)
As for many other organisms, CRISPR-Cas9 mediated genetic modification has gained increasing importance for the identification of vaccine candidates and drug targets in Neospora caninum, an apicomplexan parasite causing abortion in cattle and neuromuscular disease in dogs. A widely used approach for generating knock-out (KO) strains devoid of virulence factors is the integration of a drug selectable marker such as mutated dihydrofolate reductase-thymidylate synthase (mdhfr-ts) into the target gene, thus preventing the synthesis of respective protein and mediating resistance to pyrimethamine. However, CRISPR-Cas9 mutagenesis is not free of off-target effects, which can lead to integration of multiple mdhfr-ts copies into other sites of the genome. To determine the number of integrated mdhfr-ts in N. caninum, a duplex quantitative TaqMan PCR was developed. For this purpose, primers were designed that amplifies a 106 bp fragment from wild-type (WT) parasites corresponding to the single copy wtdhfrs-ts gene, as well as the mutated mdhfrs-ts present in KO parasites that confers resistance and were used simultaneously with primers amplifying the diagnostic NC5 gene. Thus, the dhfr-ts to NC5 ratio should be approximately 1 in WT parasites, while in KO parasites with a single integrated mdhrf-ts gene this ratio is doubled, and in case of multiple integration events even higher. This approach was applied to the Neospora KO strains NcΔGRA7 and NcΔROP40. For NcΔGRA7, the number of tachyzoites determined by dhfr-ts quantification was twice the number of tachyzoites determined by NC5 quantification, thus indicating that only one mdhfr-ts copy was integrated. The results obtained with the NcΔROP40 strain, however, showed that the number of dhfr-ts copies per genome was substantially higher, indicating that at least three copies of the selectable mdhfr-ts marker were integrated into the genomic DNA during gene editing by CRISPR-Cas9. This duplex TaqMan-qPCR provides a reliable and easy-to-use tool for assessing CRISPR-Cas9 mediated mutagenesis in WT N. caninum strains.